2008
DOI: 10.1590/s0102-76382008000300011
|View full text |Cite
|
Sign up to set email alerts
|

Dupla artéria torácica esqueletizada versus convencional na revascularização do miocárdio sem CEC em diabéticos

Abstract: Dupla artéria torácica esqueletizada versus convencional na revascularização do miocárdio sem CEC em diabéticosDouble skeletonized internal thoracic artery vs. double conventional internal thoracic artery in diabetic patients submitted to OPCAB Abstract Objective: To evaluate the influence of the technique used in the dissection of thoracic arteries in the evolution of diabetic patients submitted to OPCAB.Methods: Seventy diabetic patients submitted to OPCAB using bilateral thoracic arteries were evaluated. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Rev Bras Cir Cardiovasc 2009; 24 (2): [157][158][159][160][161][162][163][164] the sternum [15,16], as observed recently in our country [17].…”
Section: Santos Filho Ec Et Al -Should the Diabetics Have The Internmentioning
confidence: 74%
“…Rev Bras Cir Cardiovasc 2009; 24 (2): [157][158][159][160][161][162][163][164] the sternum [15,16], as observed recently in our country [17].…”
Section: Santos Filho Ec Et Al -Should the Diabetics Have The Internmentioning
confidence: 74%
“…During the next decade, there were mainly observational studies and few randomized clinical trials comparing on and off pump coronary artery surgery in terms of morbidity, mortality, inflammatory response, patency rates, stroke, blood transfusion, costs, hospital mortality in high risk patients, and others [30][31][32][33][34][35][36][37][38][39][40][41]. Controversial results from these studies led to different opinions regarding the routine application of off pump coronary surgery [42][43][44][45][46][47][48].…”
Section: IVmentioning
confidence: 99%
“…Recent studies found that diabetic patients may present high sternum infectious complication rates if they make use of the dissected ITA pedicle [8,9]. However, Santos Filho et al [10] showed that in this group of patients, sternal perfusion is lower than in non-diabetics, justifying a higher rate of infectious complications.…”
mentioning
confidence: 99%
“…However, Santos Filho et al [10] showed that in this group of patients, sternal perfusion is lower than in non-diabetics, justifying a higher rate of infectious complications. Alternatively, when the ITA is dissected in a skeletonized fashion, sternal perfusion, with the use of scintigraphy, does not suffer a significant reduction, which seems to be the reason to reduce rates of infectious complications of the sternum and mediastinal disorders in diabetic patients in which two ATI were used [8,9].…”
mentioning
confidence: 99%